Electrospinning of Core-Shell Fibers for Drug Release Systems - Pedersbæk, D.; Frantzen, M. Tudsborg; Fojan, P. (Journal of Self Assembly and Molecular Electronics, 2023)
Electrospinning is a promising method for the fabrication of fibers used for drug release system, due the ease of operation of the electrospinning process and the high surface to volume ratio, high loading capacity and high encapsulation efficiency of the obtained fibers. In this study release of tetracycline hydrochloride (TCH) from both monolithic and core-shell electrospun fibers of poly-lactic acid (PLA), poly--caprolactone (PCL) and their blend were studied. It was found that the drug release from the fibers depended on their composition. Core-shell fibers were designed with PCL and TCH in the core and with blends (PCL/PLA) of varying composition in the shell. A varying initial burst release was observed when the composition of the shell was varied. This illustrates that the burst release might be tunable which can be advantageous for many applications